Penyusunan Training Matrix Setiap Job Title Berdasarkan Job Description pada Divisi Manufacturing PT Ecogreen Oleochemcials - Sitanggang, Rio Iriando Hasudungan; Bendatu, Liem Yenny (Jurnal Titra, 2014)
Ecogreen Oleochemicals is one of the companies engaged in the field of oleochemicals andÂ  produces some olechemicals products. Company has been providing some trainings held by Human Resources Department based on userâs request. The userâs request is not effective because it is not suitable with training needs of employee. Therefore, usingÂ  job description approach into training matrix can define the training needs of an employee clearly. Training matrix consists of technical competency and knowledge. Total of training matrix in Manufacturing Division are 68 which divided into 19 in Maintenance Department, 15 in Production EOB 1, 8 in Production EOB 2, 4 in Quality Assurance, 4 in Utility, 18 in Engineering. Knowledge mapping will be used as a guidance for Human Resources Department to arrange the training